2004
DOI: 10.1196/annals.1316.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Substance Abuse Vulnerability: Remarkable Recent Convergence of Genome Scan Results

Abstract: Classical genetic studies document strong complex genetic contributions to abuse of multiple addictive substances. Goals of molecular genetic studies of addiction include: (1) locating chromosomal regions that contain allelic gene variants that contribute to vulnerability to drug dependence and (2) discovering which alleles of which gene markers and which genes provide these enhanced vulnerabilities. Genome scanning provides an approach to these goals. Until recently, data from genome scanning studies did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 42 publications
5
49
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Only a few of the results of these studies have converged convincingly, with the major linkage peak produced by a number of studies being poorly, if at all, supported by subsequent data (e.g., see [22][23][24][25][26] ). Indeed, assemblies of current results from at least some linkage-based genomes can produce results that cover the majority of the genome with data that derive from at least some reported linkage peak in at least one study (C Johnson, GR Uhl, unpublished observations, 2005).…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30][31][32][33][34] Only a few of the results of these studies have converged convincingly, with the major linkage peak produced by a number of studies being poorly, if at all, supported by subsequent data (e.g., see [22][23][24][25][26] ). Indeed, assemblies of current results from at least some linkage-based genomes can produce results that cover the majority of the genome with data that derive from at least some reported linkage peak in at least one study (C Johnson, GR Uhl, unpublished observations, 2005).…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%
“…These "reproducibly positive" markers (Table 1) clustered much closer to positive markers from linkage studies of addictions than anticipated by chance. [33][34][35] However, this total of 13,015 SNPs provided information about possible associations with addiction for only a modest number of the blocks of restricted haplotype diversity found in these subjects' genomes and thus only modest power (FIG. 1).…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%
“…In a recent study of Colorado adolescents, Young et al, (2006) found high heritability for tobacco use (0.46), marijuana use (0.44), problem alcohol use (0.70) and problem marijuana use (0.64). Other studies have also shown that genetic and environmental factors may contribute to a general predisposition to illicit drug use rather than a substance-specific effect (Kendler et al, 2003;Karkowski et al, 2000;Agrawal et al, 2004;Uhl, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome linkage analysis using moderately sized marker panels and LOCUSBASED LINKAGE on families that are derived from the cosmopolitan population of the United States and from population isolates has yielded replicated linkages to chromosomal regions 27 , even when these studies have used heterogeneous definitions such as alcohol dependence 23,28 , antisocial alcoholism 24 or alcoholism with depressive syndrome 29 . Whole-genome scans using the allele-based LINKAGE DISEQUILIBRIUM approach have been carried out for addictions 30 using a relatively small panel of SNP markers.…”
Section: Gene Identification: Positional Cloningmentioning
confidence: 99%